1996
DOI: 10.1002/(sici)1097-4644(19960401)61:1<9::aid-jcb2>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces TGF‐β1 activity and apoptosis of human MCF‐7 breast cancer cells in vitro

Abstract: We report here that the antiestrogen tamoxifen (TAM) induces cell death in human breast cancer cell line MCF-7. We assessed the type of cell death induced by TAM in this breast cancer cell line on the basis of morphological and biochemical characteristics. Dying cells showed morphological characteristics of apoptosis, such as chromatin condensation and nuclear disintegration. DNA isolated from these cells revealed a pattern of distinctive DNA bands on agarose gel. The DNA fragmentation in MCF-7 cells induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…A third possibility is that the cells responding to droloxifene/estradiol are neither in the osteoblastic nor osteoclastic lineages but are secreting a cytokine such as TGF-b that induces apoptosis in pre-osteoclastic cells. A recent report showed that tamoxifen induced TGF-b1 activity and apoptosis in human MCF-7 breast cancer cells in vitro [Chen et al, 1996].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A third possibility is that the cells responding to droloxifene/estradiol are neither in the osteoblastic nor osteoclastic lineages but are secreting a cytokine such as TGF-b that induces apoptosis in pre-osteoclastic cells. A recent report showed that tamoxifen induced TGF-b1 activity and apoptosis in human MCF-7 breast cancer cells in vitro [Chen et al, 1996].…”
Section: Discussionmentioning
confidence: 98%
“…al., 1991]. Droloxifene's antagonism of breast cancer cell growth might also be achieved through apoptosis as has been reported for tamoxifen [Chen et al, 1996]. MCF-7 cells treated with either droloxifene or 17b-estradiol (10 28 M) were assayed for cellular apoptosis using TUNEL.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamoxifen is a selective ER modulator that is used for the treatment of estrogen-dependent breast cancer. The cytotoxic effect of tamoxifen depends on not only suppression of ER activity but also autocrine induction 23,24 of TGF-β1. Because FOXA1 is highly expressed in ER-positive breast cancer cells, FOXA1 is thought to suppress the cytotoxic effect of tamoxifen by inhibiting TGF-β1-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ER antagonist tamoxifen promotes apoptosis of ERpositive breast cancer cells, and this cytotoxic effect depends on autocrine induction of TGF-β1. 23,24 We then examined the effect of FOXA1 knockdown on tamoxifeninduced apoptosis of ER-positive MCF7 cells. FOXA1 knockdown significantly enhanced cell death induced by tamoxifen treatment in MCF7 cells ( Figure 6A).…”
Section: Foxa1 Suppresses the Cytotoxic Effect Of The Breast Cancermentioning
confidence: 99%